2023
DOI: 10.1111/1365-2664.14399
|View full text |Cite
|
Sign up to set email alerts
|

Spillover of chalkbrood fungi to native solitary bee species from non‐native congeners

Abstract: Introduced, managed bees such as mason bees (genus Osmia) can confer significant pollination benefits to agricultural systems, but a risk of introducing non‐native species into new ecosystems is the co‐introduction of pathogens along with them. Pathogen spillover to wild, native bees may then drive native bee species declines. This study examined prevalence of the chalkbrood‐causing fungal genus Ascosphaera in the nests of both non‐native and native mason bee species. We conducted large‐scale trap‐nesting and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The numbers of such parasites could increase over time, especially if trap‐nest occupancy was to increase (Groulx & Forrest, 2018; Steffan‐Dewenter & Tscharntke, 2001; Torchio, 1979). Indeed, others have suggested that trap‐nests intended for cavity‐nesting pollinator conservation can act as ecological traps by providing habitat for parasites and encouraging the spread of pathogens (Colla, 2022; LeCroy et al., 2023; MacIvor & Packer, 2015). It would be useful to monitor Osmia populations over several years after nesting‐habitat supplementation to test whether population increases are maintained or whether they are eventually overtaken by growing numbers of parasites or pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…The numbers of such parasites could increase over time, especially if trap‐nest occupancy was to increase (Groulx & Forrest, 2018; Steffan‐Dewenter & Tscharntke, 2001; Torchio, 1979). Indeed, others have suggested that trap‐nests intended for cavity‐nesting pollinator conservation can act as ecological traps by providing habitat for parasites and encouraging the spread of pathogens (Colla, 2022; LeCroy et al., 2023; MacIvor & Packer, 2015). It would be useful to monitor Osmia populations over several years after nesting‐habitat supplementation to test whether population increases are maintained or whether they are eventually overtaken by growing numbers of parasites or pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are potential consequences that could result from these accidental introductions (Goulson 2003, Russo et al 2021. One concern would be whether the non-native species harbor any pests or diseases that could spread to native Chelostoma, particularly given that eight of the nine native North American species of Chelostoma occur in the west (LeCroy et al 2023). Routes of exposure would likely be limited to shared nesting sites and nesting resources since native Chelostoma do not use the same floral resources as the nonnative species, potentially limiting their risk.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of fungal pathogens from Japan (i.e., Ascosphaera naganensis and Ascosphaera fusiformis) has been reported in the United States in several native Osmia spp. (Hedtke et al 2015, LeCroy et al 2022. While the presence of these Ascosphaera spp.…”
Section: Biological Traits and Data Suggesting Potential For Invasive...mentioning
confidence: 99%